Desain Logo Dan Digital Marketing: Penguatan Kreativitas Siswa Di Kecamatan Muara Badak - Ferry Diyanti; Anggita Arlyne Patricia Sinaga; Yunita Fitria (CV. Multi Kreasi Media, 2025)
This Community Service (PKM) activity aims to introduce and strengthen logo design and digital marketing through mentoring activities carried out directly to students in Muara Badak District. Logo creation is considered important because it will impact the selling value of the product itself, while digital marketing functions to expand market share. This activity has five stages: problem analysis, collaboration with related parties, activity preparation, implementation, and evaluation of results. The implementation of the activity has run smoothly. The evaluation results show that students, as participants in the activity, have understood the importance of logos and digital marketing in helping increase product sales. They can also utilize the potential of e-commerce and social media to help market products to gain a wider market share.